ABCG2/BCRP: variants, transporter interaction profile of substrates and inhibitors. (3rd April 2019) - Safar, Zsolt; Kis, Emese; Erdo, Franciska; Zolnerciks, Joseph K; Krajcsi, Peter
ABSTRACT: Introduction : ABCG2 has a broad substrate specificity and is one of the most important efflux proteins modulating pharmacokinetics of drugs, nutrients and toxicokinetics of toxicants. ABCG2 is an important player in transporter-mediated drug–drug interactions (tDDI). Areas covered : The aims of the review are i) to cover transporter interaction profile of substrates and inhibitors that can be utilized to test interaction of drug candidates with ABCG2, ii) to highlight main characteristics of in vitro testing and iii) to describe the structural basis of the broad substrate specificity of the protein. Preclinical data utilizing Abcg2/Bcrp1 knockouts and clinical studies showing effect of ABCG2 c.421C>A polymorphism on pharmacokinetics of drugs have provided evidence for a broad array of drug substrates and support drug – ABCG2 interaction testing. A consensus on using rosuvastatin and sulfasalazine as intestinal substrates for clinical studies is in the formation. Other substrates relevant to the therapeutic area can be considered. Monolayer efflux assays and vesicular transport assays have been extensively utilized in vitro. Expert opinion : Clinical substrates display complex pharmacokinetics due to broad interaction profiles with multiple transporters and metabolic enzymes. Substrate-dependent inhibition has been observed for several inhibitors. Harmonization of in vitro and in vivo testing makes sense. However, rosuvastatin and sulfasalazine are not efficiently transported in either MDCKII or LLC-PK1-based monolayers. Caco-2 monolayer assays and vesicular transport assays are potential alternatives.